Cambrian-Middle Ordovician Platform-Slope Stratigraphy, Palaeontology and Geochemistry of Western Newfoundland - Svend Stouge; Gabriella Bagnoli; Duncan McIlroy (Geological Survey Newfoundland and Labrador, 2017)
Newfoundland and Labrador is located on the eastern edge of North America (Figure 1). The island of Newfoundland, known to it’s friends as “The Rock”, lies off the east coast of the North American mainland, and is the most populous part of the Canadian province of Newfoundland and Labrador. The island is only 29% of the total province's land area (111,390 km2), but is still comparable to the size of the three maritime provinces of Nova Scotia, New Brunswick, and Prince Edward Island combined. The island is separated from Labrador by the Strait of Belle Isle and the Gulf of St. Lawrence. Newfoundland's nearest neighbour is the French colony of Saint-Pierre and Miquelon, which lies opposite the GSSP for the Ediacaran–Cambrian boundary at Fortune on the Burin Peninsula (where one of the post-conference field excursions associated with ISECT 2017 will go). Though Newfoundland and Labrador is larger than some countries, it has a small population of 510,000, around half of whom live in the greater St. John's area. The Communities of Rocky Harbour and Norris Point are enclaves within Gros Morne National Park, and form a rich local scientific and artistic hub on the west coast of Newfoundland. Many of the localities we visit will be within Gros Morne National Park (a UNESCO World Heritage Site). Collecting and hammering is not permitted at these localities. Your guides will be explicit about when you are within Gros Morne National Park.The terrain of Newfoundland and Labrador varies from arctic tundra, ancient mountain ranges, lush boreal forest to rugged coastline. In Gros Morne National Park you will see the direct evidence for plate tectonics, and get a chance to step on rocks from the earth's mantle. The presence of the ophiolite is one of the reasons for Gros Morne National Park’s existence, as it was the first place that field evidence for plate tectonics was demonstrated. On the east coast of Newfoundland, where many of us will go for the formal meetings of the Ediacaran and Cambrian commissions, there are other ...